Methodologies and moderator-mediating factors of integrated reporting: a systematic review - O Alatawi, Mohammed Saleem; Mat Daud, Zaidi; Johari, Jalila (Society of Cultural Studies and Social Sciences, Hong Kong, 2023)
This systematic review paper aims to provide an overview of the content literature review of integrated reporting in the following categories: (1) the methodology approach used; (2) the mediating-mediator factors of integrated reporting. Using a systematic literature review design based on PRISMA guidelines, the data were collected from selected databases (google scholar). The study reviewed 52 papers. The timeframe of the study was from 2017 until 2023 (May). The findings of the reviewed articles showed that the majority of the papers were published in Emerald publisher journals (25). The highest number of articles were published in 2022 (25 articles). Most of the papers employed a quantitative research design and selected secondary data that was followed by a mixed-method research design. The moderator and mediating factors found in the reviewed articles were needs for external financing, corporate Social responsibility, earnings per share (EPS), firm complexity, financial leverage (low but significant), environmental, social and governance (ESG) performance reporting, board gender diversity and family firms, CEO integrity, and CEO power, while only two mediating factors were found: Integrated reporting, and firms’ reputation. Based on the findings, the study suggests several implications and suggestions for delivering better knowledge of integrated reporting.